KEDUDUKAN HUKUM PERJANJIAN PERKAWINAN SEBAGAI ALASAN PERCERAIAN - Abdul Rokhim (Masalah-Masalah Hukum, 2012)
Judicially, made agreement generate legal consequences and related/relevant the parties entitled to raise cancellation of contract or making [him/ it] as reason of divorce, made agreement fasten both parties and become law for the man who making its meaning it if agreement of marriage made is laterthen impinged by one of the parties hence party side which feel themselves aggrieved and cannot accept [the] mentioned can be raised as reason of divorce. Thereby that agreement of marriage made by spouse and legalized [by] before officer of marker do (PPN marriage), since ratifying of the agreement hence the agreement with power of law and become [is] obliged to be executed. In Islamic Law Compilation (KHI), please explained that made agreement can in the form of talaq taklik which is inveterate to be said by husband after legalization of marriage and other agreement which not illegal Islam, the agreement can in the form of dissociation of community property, or other agreement which its contents not trespass law order, ethics and religionKeywords : Agreement, Divorce